Ang kasaysayan sang komentaryo sa kahanginan the evolution of Bombohanay Bigtime in DYFM Bombo Radyo iloilo - Germia, Rhea Jane D.
This thesis is made to document the evolution of DYFM Bombo Radyo Iloilo?s Bombohanay Bigtime since the 1980s and produce a 3-episode expository documentary. Data collection is made through expert interview using purposive and snowball sampling and employing the theories Organizational Culture by Nick O?Donnell and Michael Pakanowsky and Agenda-Setting by Maxwell McCombs and Donald Shaw. The results show that the patterns exhibited in the commentary program Bombohanay Bigtime are manifested in content element, people and production element. Moreover, operating environment, current leadership, early dominant leaders, and the national culture are the factors that affect the said program. The researches conclude that ?Sari-sari? format and capsulized commentaries are consistently observed in the program. Commentators of the program are all male characterized to be bombastic, hard-hitting, and straightforward in their manner of delivery as these qualities usually evoke a sense of command and authority. Furthermore, despite technological changes, the hitting of the drum to emphasize certain points or arguments during Bombohanay Bigtime continues to serve as the identity of the program. However, DYFM Bombo Radyo Iloilo management is open to innovation as it continues to adapt to technological advancements. The proponents of this study recommend that archiving be properly observed by the station to preserve important information. Furthermore, studies focusing on the people element, particularly the changes in the manpower of the station should also be taken into consideration.